HUBUNGAN KEMAMPUAN MATEMATIKA TERHADAP PRESTASI BELAJAR SISWA DALAM PEMECAHAN MASALAH PADA KINEMATIKA ANALISIS VEKTOR DI SMA NEGERI 4 BANDA ACEH - Musdar Musdar (Syiah Kuala University, 2015)
There are several factors that cause learning physics student achievement scores are low, one of which was the lack of mathematical skills possessed by students. Physics as one of the fields of study abstract is more easily understood and solved the problem when used concepts shaped mathematical physics. In this case the math skills used in solving problems on kinematics material Vector Analysis. In other words, the relationship between mathematical ability and academic achievement of students in solving physics problems on kinematics material Vector Analysis. The purpose of this study was to determine the relationship between mathematical skills with student achievement in problem solving on kinematics material Vector Analysis in SMAN 4 Banda Aceh. The data collection is done by means of documentation and test physics problem. Data analysis using product moment correlation and t-test. The results of data analysis showed prices and t_hitungr_xy = 0.765 = 5.17. At the significant level α = 0.05 with degrees of freedom df = (N-2) = 29, then from the distribution list obtained t_tabel t = 2.09. Can be explained that Ho is rejected if t_hitungt_tabel (5.17 2.09) and Ha accepted. Thus, there is a significant positive relationship between mathematical ability and academic achievement of students in solving problems on kinematics material Vector Analysis in SMAN 4 Banda Aceh.